Soluble and Insoluble Varnish Test Methods for Trending Varnish Buildup in Mineral Turbine Oil - Wasan CHOKELARB; Pornsawan ASSAWASAENGRAT; Andy SITTON; Thanant SIRISITHICHOTE; Pongsert SRIPROM (My University, 2022)
Varnish problems in turbine oil of power plants in Thailand are still an issue today. The problems are the coefficient of friction of the oil will increase along with the increase in varnish concentration and varnish deposits. This creates problems in starting/re-starting of the turbine. Even with the advent of oil manufacturing research to improve base oil quality and antioxidant additive, varnish contamination starting problems have been one of the most concerning problems for maintenance. The most recent version of ASTM D4378-20 suggests that maintenance personnel should test their in-service turbine oil and monitor the membrane patch colorimetry with a warning limit at ∆E 30. This monitoring test is known as ASTM D7843-20 Standard Test Method for Measurement of Lubricant Generated Insoluble Color Bodies in In-Service Turbine Oils using Membrane Patch Colorimetry (MPC). This study introduces the monitoring of soluble color bodies, in addition to the insoluble, at the same time. Focusing only on the value of insoluble-MPC test can sometimes be misleading and may cause inaccurate and ineffective maintenance decisions. In this paper, both soluble and insoluble color body analytical results from in-service gas turbine oils will be presented. Three power plants were monitored for both soluble and insoluble varnish. It will show how the use of a combination of soluble and insoluble color body assessments of the turbine oils would further improve the oil diagnostic services of turbine lubricants by providing insights into the capability of the lubricants to solubilize the oxidation by-products of the antioxidants and the highly refined base oil. Appropriate varnish removal technologies were also decided and applied to respond proactively to the varnish issues.
Keywords: Mineral oil; Colorimetry; Lubricants and Their Additives